Tumour stage and resection margin status are independent survival factors following partial pancreatoduodenectomy for duodenal adenocarcinoma - Mann, Kulbir; Gilbert, T.; Cicconi, S.; Jackson, R.; Whelan, P.; Campbell, F.; Halloran, C.; Neoptolemos, John P.; Ghaneh, Paula (Langenbeck's archives of surgery, 2019)
IntroductionThere is limited published evidence on duodenal carcinoma due to its rarity. This study aimed to evaluate gastric outlet obstruction and obstructive jaundice along with pathological variables as survival factors in patients with duodenal adenocarcinoma following resection.MethodsSurvival factor analysis was undertaken in patients undergoing duodenal cancer surgery from 1997 to 2015 in a single centre.ResultsThere were 57 patients of whom 18 had gastric outlet obstruction and 14 had obstructive jaundice. Fifty-three had a partial pancreatoduodenectomy and four had palliative bypass. Perioperative mortality and morbidity were 4% (2/53) and 47% (25/53) respectively in resected patients. With a median (95% confidence interval, CI) follow-up of 72 (57-86) months, median overall and recurrence-free survival was 38 months (95% CI 28-113) and 27 months (95% CI 18-83) respectively. The 1 and 3-year overall survival rates were 84% (95% CI 74-95) and 52% (95% CI 39-69) respectively. Median overall survival was 19 months in patients with gastric outlet obstruction vs 53 months in those without (p = 0.026) and 28 months in patients with obstructive jaundice vs 38 months in those without (p = 0.611). Univariate analysis revealed that tumour stage, resection margin status, pre-operative albumin status, gastric outlet obstruction and age were associated with poorer overall and recurrence-free survival but multivariate analysis confirmed only tumour stage and resection margin status to be significant.ConclusionWhereas gastric outlet obstruction in duodenal cancer appeared to be an important survival factor following partial pancreatoduodenectomy, multivariate analysis showed that only tumour stage and resection margin status were the key independent survival factors. Further multicentre studies are required to elucidate further characteristics of duodenal carcinoma and develop neoadjuvant/adjuvant management strategies.